PROFIL PENGGUNAAN OBAT ANALGETIK BERDASARKAN RESEP DOKTER DI APOTEK KIMIA FARMA TITIBUMI - Diyah Dwi Lestari; Dwi Hastuti (Jurnal Kefarmasian Akfarindo, 2022)
Background: One of the health problems that is often faced is pain in the limbs. Pain can be overcome by using analgesic drugs. The use of analgesic drugs at Kimia Farma Titibumi Pharmacy is classified as fast moving, this is due to the location of the pharmacy which is close to clinics and practicing doctors. Almost all doctors around the pharmacy prescribe analgesic drugs. Objective: The purpose of this study was to determine the profile of the use of analgesic drugs with a doctor's prescription at Kimia Farma Titibumi Pharmacy for the period January - May 2020. Methods: The method in this research is descriptive observational research. Collecting data in the form of prescriptions containing analgesic drugs at Kimia Farma Titibumi Pharmacy for the period January - May 2020. The data were analyzed descriptively. The data results were presented in tabular form about the profile of analgesic drug use based on doctor's prescriptions at the Titibumi Kimia Farma pharmacy. Results: The results and conclusions of this study are the use of analgesic therapy the most is single therapy, namely metamizole with 35 prescriptions (21.21%), while for combination therapy, paracetamol + tramadol with 18 prescriptions (10,91%). The highest class of drugs is the non-opioid group with 122 prescriptions (73.94%). Conclusion: Of the 165 existing prescriptions, 163 prescriptions (98.79%) had the appropriate dosage, and there were 2 prescriptions (1.21%) that did not match the dosage.